Mockumentary Comedy Performing Authenticity - Wallace, Richard (Palgrave Studies in Comedy, 2018)
This book is the first to take comedy seriously as an important aspect of the popular mockumentary form of film and television fiction. It examines the ways in which mockumentary films and television programmes make visible-through comedy-the performances that underpin straight documentaries and many of our public figures. Mockumentary Comedy focuses on the rock star and the politician, two figures that regularly feature as mockumentary subjects. These public figures are explored through detailed textual analyses of a range of film and television comedies, including A Hard Day's Night, This is Spinal Tap, The Thick of It, Veep and the works of Christopher Guest and Alison Jackson. This book broadens the scope of existing mockumentary scholarship by taking comedy seriously in a sustained way for the first time. It ultimately argues that the comedic performances-by performers and of documentary conventions-are central to the form's critical significance and popular appeal. .